The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jvs.2015.06.224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of thoracic endovascular aneurysm repair using commercially available fenestrated stent graft (Najuta endograft)

Abstract: The perioperative and 3-year outcomes of TEVAR using the Najuta precurved, fenestrated endograft demonstrated high freedom from aneurysm enlargement and patency rates of the supra-aortic branches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 19 publications
0
56
1
Order By: Relevance
“…Unfixed ePTFE allows the fabric to expand along the aortic wall, allowing no need for a strong radial force for sealing. 6,7 Furthermore, this characteristic also enables limited contact of the bare stent to the intima. Minimal radial force and endoskeleton characteristics of Najuta was useful in securing the landing zone for multiple endograft while reducing the risk for SINE by reducing the stress to the native aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…Unfixed ePTFE allows the fabric to expand along the aortic wall, allowing no need for a strong radial force for sealing. 6,7 Furthermore, this characteristic also enables limited contact of the bare stent to the intima. Minimal radial force and endoskeleton characteristics of Najuta was useful in securing the landing zone for multiple endograft while reducing the risk for SINE by reducing the stress to the native aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…These fenestrations are crossed by stent-struts and are not reinforced, so that no additional stenting of these fenestrations is possible. Iwakoshi et al reported technical success rate of 91% using the Najuta stent-graft in 32 patients (27). Aneurysm-related rate and rate of freedom from secondary intervention at 3 years were 97% and 84%, respectively (27).…”
Section: Najuta Fenestrated Stent-graft (Kawasumi Laboratories Inc)mentioning
confidence: 99%
“…However, the reintervention rate was relatively high at 10%. 34,35 The devices of both a-Branch and Bolton dual-branch aortic arch endografts have two inner sleeves for reconstructing the BCA and LCCA. The preliminary results of 26 patients undergoing branched TEVAR with Bolton dual-branch graft revealed a 30-day mortality of 7.7% and postoperative stroke in 3.8% of cases.…”
Section: Distal Arch and Aortic Arch Aneurysmmentioning
confidence: 99%